Response to 'A call to standardize the BCC:SCC ratio': reply from the authors. (27th July 2021) - Jiyad, Z.; Marquart, L.; Green, A.C.
Abstract : Linked Articles: Ma et al. Br J Dermatol 2021; 185 :868–869 ; Jiyad et al. Br J Dermatol 2021; 184: 545 .